Powerful Explosions from the Collapse of Rotating Supermassive Stars - Sho Fujibayashi; Cédric Jockel; Kyohei Kawaguchi; Yuichiro Sekiguchi; Masaru Shibata (The Astrophysical Journal)
We perform new general relativistic hydrodynamics simulations for collapses of rotating supermassive star cores with an approximate nuclear burning up to carbon and a detailed equation of state. For all the models we investigate, the energy generation by nuclear burning plays only a minor role, leading to the formation of a black hole without a nuclear-powered explosion. For rotating models, however, the stellar explosion associated with shock heating is driven from a torus, which forms after the black hole formation. The explosion energy is up to 10 ^−4 of the mass energy of the supermassive star cores (∼10 ^55 –10 ^56 erg). We find that, even if we increase the rotational angular momentum of the progenitor, the ejecta mass saturates at ∼1% of the total mass of the initial stellar core. The average ejecta velocity also saturates at ≈20% of the speed of light. As a result, the ejecta kinetic energy is approximately proportional to the initial mass of the supermassive star core for the rapidly rotating case. We also perform viscous hydrodynamics simulations to explore the evolution of the remnant torus. Although the viscous heating drives an outflow from the torus, we find that its effect is subdominant in terms of the kinetic energy because of the small velocity (≈0.07 c ) of the ejecta component.